Utilización de los espacios dinámicos dentro del aula como fuente de desarrollo cognitivo y social en los niños de cuarto grado de EGB de la Unidad Educativa “Vicente Rocafuerte”, cantón Guaranda, provincia bolívar, período 2021 – 2022 - Chimbo Chimbolema, Debora Diana (2022)
This research work analyzed the reality of children in the fourth grade of EGB parallel "B", of the Educational Unit Vicente Rocafuerte, regarding the use of dynamic spaces as a source of cognitive and social development. The investigation corroborated the use of spaces and the use of teaching materials within the classroom to create learning environments. By measuring observation as a technique and the field journal as an instrument to record the information collected, the study results show the need to strengthen learning environments with didactic resources, due to its favorable impact on the teaching-learning process, such as the development of cognitive and social skills in students. A space with favorable conditions and resources for children to build their own knowledge through educational experiences. Keywords: Dynamic Spaces, Class, Cognitive Development, Social Development.